Apakah Penghindaran Pajak dan Faktor Internal Perusahaan Berpengaruh Terhadap Nilai Perusahaan di Indonesia? - Ali Abrori; Puji Wahono; Indra pahala (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Taxes and death, as Benjamin Franklin famously stated, are two certainties in life, including for companies as legal entities. In some cases, taxes significantly impact firm value, particularly through tax avoidance strategies. The success or failure of a company can often be reflected in its firm value. Other factors believed to influence firm value include some firm’s internal factors, such as solvability, company size, profitability, and liquidity. This study aims to examine these factors and their impact on the value of companies listed in the industrial subsector of the Indonesian stock exchange from 2019-2022. Using purposive sampling, a sample of 55 firm-years data was tested using multiple linear regression with SPSS 26. The study found that tax avoidance, proxied by the Effective Tax Rate (ETR), has a negative and significant effect on firm value. Among the four internal factors, only profitability, proxied by Return on Assets (ROA), has a positive and significant impact on company value. The other three variables—solvability proxied by Debt-to-Equity Ratio (DER), company size (SIZE) proxied by total asset, and liquidity proxied by current ratio (CR)—do not significantly affect firm value.